IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT THROUGH PEGWORD STRATEGY FOR THE YEAR-2 STUDENTS AT SMPN 9 KENDARI - Yasin, Yustih (Aksara Public, 2019)
The objective of this study is to improve students’ vocabulary achievement at class VIII-6 of SMPN 9 Kendari through Pegword Strategy. The researcher finds some problems faced by students at VIII-6 class of SMPN 9 Kendari on learning vocabulary. Those problems are find offer the researcher do preliminary research through direct observation, interviewing some students and the English teacher, and giving diagnostic test. The problems of the students difficulty to determine the word class of vocabulary, do not know synonym and antonym of vocabularies, do not know vocabulary use, easy to forget the vocabularies which they have learned, rare to apply new vocabularies which they get, and do not have a good way to learn vocabulary. The subject of this study is VIII-6 class of SMPN 9 Kendari in academic year 2017/2018. The total subjects are 35 students. The design of this study is classroom action research. This study is conducted in two cycles which applied some instruments. They are vocabulary tests in form of objective test, observation sheet, and note taking. The target vocabulary of this study are verb, noun, and adjective (contents word). In this research, qualitative and quantitative data are collected and analyzed by describing data into words and by using descriptive statistics. As the result of this study, the writer finds that in diagnostic test, the mean score is 51.7. In the first cycle, the mean score of the vocabulary test is 75.30 with the average of target improvement is 68.57 %. While for the cycle two, the mean score of the vocabulary test is 82.98 with the average of target improvement is 94.28 %. In other words, it could be said that there is an improvement about 7.68 in the cycle two compared to the mean score of vocabulary test in the cycle one and about 25.71 % improvement of the target of study. This result indicates that the Pegword Strategy can improve students’ vocabulary achievement class VIII-6 of SMPN 9 Kendari.